Liver fluke infestation in Kansas fed slaughter cattle - Laudert, S.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feedlot cattle from 1,687 pens totaling 290,183 head were evaluated at slaughter for the presence of liver flukes. Overall, 4.92% of the cattle were found to be infected. Only 15.2% of all pens of cattle were found to be completely free of flukes. However, only 5.3% of the pens had greater than 15% of the cattle infested. Beef steers had a higher level of infestation (5.2%) than beef heifers (4.4%). Holstein steers had an overall infestation rate of 4.4%.
Keywords: Beef; Liver fluke; Slaughter cattle